The Impacts of Requirements of Applying Knowledge in Improving the Quality of Educational Services (A Field Study in Tishreen University) (Journal of Hama University, 2019)
The researcher in this study is examining the impact of applying knowledge on the quality of educational services in Tishreen University. The study sample includes (319) members of the academic staff at Tishreen University. The questionnaire is the main tool for collecting data. Some interviews are conducted to inquire about some issues. The data is analyzed using the statistical program (SPSS 20).The main purpose of this study was to highlight the impact of knowledge application requirements on improving the quality of educational services, highlighting the significance of the requirements and the need to apply them in the university in order to improve the quality of the provided educational services .One of the main results of the study is that there is a  positive relationship between relying on knowledge application requirements and improving the quality of  the provided educational services. Thus, the more relying on knowledge and paying attention to the requirements of its application, the more it will improve the quality of the provided educational services. This is clear in the field study that the application requirements of knowledge contribute to a total interpretation difference (53.248%) of the total variance or change in improving the quality of educational services at Tishreen University. The results show that (Information Technology) had the greatest impact on improving the quality of the provided educational services with effect (1,489), followed by (organizational culture) with effect (0.677).